Feasibility and reliability of an automated controller of inspired oxygen concentration during mechanical ventilation - Saihi, Kaouther (BioMed Central, 2014)
INTRODUCTION: Hypoxemia and high fractions of inspired oxygen (FiO(2)) are concerns in critically ill patients. An automated FiO(2) controller based on continuous oxygen saturation (SpO(2)) measurement was tested. Two different SpO(2)-FiO(2) feedback open loops, designed to react differently based on the level of hypoxemia, were compared. The results of the FiO(2) controller were also compared with a historical control group. METHODS: The system measures SpO(2), compares with a target range (92% to 96%), and proposes in real time FiO(2) settings to maintain SpO(2) within target. In 20 patients under mechanical ventilation, two different FiO(2)-SpO(2) open loops were applied by a dedicated research nurse during 3 hours, each in random order. The times spent in and outside the target SpO(2) values were measured. The results of the automatic controller were then compared with a retrospective control group of 30 ICU patients. SpO(2)-FiO(2) values of the control group were collected over three different periods of 6 hours. RESULTS: Time in the target range was higher than 95% with the controller. When the 20 patients were separated according to the median PaO(2)/FiO(2) (160(133-176) mm Hg versus 239(201-285)), the loop with the highest slope was slightly better (P = 0.047) for the more-hypoxemic patients. Hyperoxemia and hypoxemia durations were significantly shorter with the controller compared with usual care: SpO(2) target range was reached 90% versus 24%, 27% and 32% (P < .001) with the controller, compared with three historical control-group periods. CONCLUSION: A specific FiO(2) controller is able to maintain SpO(2) reliably within a predefined target range. Two different feedback loops can be used, depending on the initial PaO(2)/FiO(2); with both, the automatic controller showed excellent performance when compared with usual care. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/cc13734) contains supplementary material, which is available to authorized users.